Improving Students Listening Skills Using BBC Learning English Website - Yeni Anggrayni; Dahnilsyah; Afrianto Daud (International Journal of English and Applied Linguistics (IJEAL), 2024)
This classroom action research aims to investigate the improvement of students' listening skills using the BBC Learning English website. The participants of this research were the eleventh grade of an integrated Islamic high school in Pekanbaru in the academic year 2023/2024. The participants were selected purposively, that is XI IPA class consists of 27 students. An observation checklist and field notes were used to collect qualitative data. Meanwhile, the quantitative data were collected by conducting the listening test and the percentage of students’ observations. The data was analyzed using Microsoft Excel to calculate the average score, percentage of students’ achievements in listening tests, and percentage scores of students’ observations. This study found that the students’ average score in Cycle 1 (87.5%) was higher than the students’ average score in the baseline data (12.5%). Based on the observation, the students were enthusiastic during the teaching and learning process. This means that BBC Learning English has proven to be effective in improving students’ listening scores. These findings suggest that BBC Learning English is a recommended website to be used by English teachers for teaching English at senior high schools because BBC Learning English is a beneficial learning medium for increasing students’ motivation to learn English, especially in motivating students to improve their listening skills.